2014
DOI: 10.4314/ajtcam.v11i3.25
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive, Anti-Inflammatory and Antipyretic Activities of the Leaf Methanol Extract of <i>Ruta Graveolens</i> L. (Rutaceae) in Mice and Rats

Abstract: Background: Ruta graveolens has been used to treat toothache, earache, rheumatism and fever with little scientific evidence corroborating these uses. Materials and Methods:The leaf methanol extract of Ruta graveolens was evaluated for antinociceptive activity using the acetic acid writhing and hot-plate tests in mice, also anti-inflammatory and antipyretic activities using the carrageenan-induced oedema and E. coli-induced pyrexia tests in rats, respectively. Results: R. graveolens (100 mg/kg, i.p.), significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 29 publications
0
8
0
2
Order By: Relevance
“…Many studies reported the anti‐inflammatory activity of Ruta graveolens [35,36] . In a research conducted by Loonat and Amabeoku, [35] the extract of R. graveolens significantly reduced carrageenan‐induced edema.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies reported the anti‐inflammatory activity of Ruta graveolens [35,36] . In a research conducted by Loonat and Amabeoku, [35] the extract of R. graveolens significantly reduced carrageenan‐induced edema.…”
Section: Resultsmentioning
confidence: 99%
“…Rue should not be used internally due to toxicity issues. The data obtained by Loonat and Amabeoku (2014), indicated that Ruta graveolens has antinociceptive, anti-inflammatory and antipyretic activities, justifying the use of the plant species by traditional medicine practitioners in the management and treatment of pain, inflammation and fever, indicated the same authors.…”
Section: What Does the Bibliography Say About Garden Cress (Lipidium mentioning
confidence: 86%
“…The HPLC operating conditions were programmed to give the following: 0 min, solvent B: 20%; 5 min, solvent B: 40%; 15 min, solvent B: 60%; 20 min, solvent B: 80% and 27 min. The run rate was 30 min [ 44 ].…”
Section: Methodsmentioning
confidence: 99%